자궁내막암에서 세포주기 조절과 관련된 TRPC 채널의 발견 - Jang Dongmin (The Graduate School, Ajou University, 2015)
Transient receptor potential (TRP) C channels are 〖Ca〗^(2+)-permeable non-selective cation channels, relaying a variety of stimuli to intracellular Ca2+ changes. 〖Ca〗^(2+) as a second messenger has diverse functions including control of gene expression, cell cycle, cell growth, cell death, and cell differentiation. Here, we aimed to ensure whether there is a relationship between TRPC channel expression and cell cycle progression in human endometrial cancer. Two non-selective TRPC channel blocker 2-APB and SKF-96365 hinder the cell proliferation as evidenced by MTT assay. The mRNAs of TRPC1 and TRPC6 were detected in human endometrial cancer AN3CA and KLE cells. To verify a relationship between TRPC channel expression and cell cycle progression, AN3CA cells was arrested at G1 phase and at G2/M phase through cell synchronization by utilizing mimosine and nocodazole, respectively, and concomitant expression level of TRPC1 and TRPC6 mRNAs were measured by RT-PCR. Results demonstrated the expression of TRPC1 and 6 channels were regulated in a cell cycle-dependent manner with the highest expression shown at G2/M phase. The TRPC6 channels were mainly localized to the cell membrane. In addition, G2/M phase arrest induced by non-specific TRPC channel blocker SKF-96365 led to apoptotic cell death. These results suggest that TRPC channels play an important role in regulation of cell cycle of endometrial cancer. The blocking of TRPC channels causes a cell cycle arrest and apoptotic cell death subsequently.
학위논문(석사)--아주대학교 일반대학원 :생명과학과,2015. 2
Keywords: Endometrial cancer; Cell cycle; TRPC channel